Comparative efficacy of nebulization with 3% hypertonic saline and 0.9% normal saline in the management of acute bronchiolitis - Singh, Sushmita; Masand, Rupesh; Sharma, Girdhari Lal; Mehta, Swati (Indian Journal of Child Health, 2020)
Background: There is a dearth of therapeutic modalities for the management of bronchiolitis in children. Objective: The objective of the study was to compare the improvement in clinical severity scores and the length of hospital stay (LOS) among children with bronchiolitis nebulized with either 3% hypertonic saline (HS) or 0.9% normal saline (NS). Materials and Methods: A total of 360 hospitalized patients of age 1–24 months, diagnosed as a case of acute bronchiolitis of moderate severity, were randomized to receive either 4 ml of 3% HS (Group A) or 4 ml of 0.9% NS (Group B) along with 1.5 mg of epinephrine in each arm, at 4 hourly intervals till the patients were ready for discharge. Appropriate statistical analysis was carried out using the collected data. Results: All the baseline characteristics were similar in both the groups. There was a significant (p=0.0011) reduction of 13 h (12.2%), i.e., from 4 days 23 h in Group B (NS) to 4 days 10 h in Group A in the mean LOS and significant difference (p=0.0001) in the clinical severity score was noted from the 2nd day onward in Group A as compared to Group B. No adverse events were observed or reported by the treating medical team or the patients’ caregiver in both the study groups. Conclusion: Nebulization with 3% HS is superior to 0.9% NS nebulization in infants with clinically diagnosed acute bronchiolitis.